HOT WORK CLIMATE AS AN OCCUPATIONAL ENVIRONMENTAL HEALTH RISK ASSOCIATED WITH FATIGUE AMONG PARKING TICKET ATTENDANTS IN MEGAMAS AREA, MANADO - Thesalonika Elisabeth Loucianna Sunkudon; Oksfriani Jufri Sumampouw; Vennetia Ryckerens Danes (International Journal of Multidisciplinary Reseach, 2026)
Work fatigue is an important problem in occupational health that can decrease productivity and increase the risk of work errors. One of the factors that plays a role is the hot work climate, especially in semi-enclosed workspaces with limited ventilation. This study aims to analyze the relationship between hot work climate and work fatigue in parking ticket officers in the Manado Megamas Area. The study used an analytical quantitative design with a cross-sectional approach on 63 respondents. Hot work climate was measured using a heat stress monitor (WBGT), while work fatigue was measured using the KAUPK2 questionnaire. Data analysis was carried out univariate and bivariate using the Pearson correlation test. The results showed that most respondents experienced moderate fatigue (57.1%) and the highest exposure to the hot work climate was found in the morning shift (29.8°C). There was a significant association between hot work climate and work fatigue (p = 0.001; r = 0.401), with moderate correlation strength. The study shows that even though heat exposure is still below the threshold value, working environment conditions still contribute to worker fatigue. Therefore, it is necessary to control the working environment through ventilation improvements, the provision of local cooling, and adaptive work-break arrangements.